Bulletproof wireless security GSM, UMTS, 802.11 and ad hoc security. - Chandra, Praphul
Finally--a single volume guide to really effective security for both voice and data wireless networks! More and more data and voice communications are going via wireless at some point between the sender and intended recipient. As a result, truly "bulletproof" wireless security is now more than a desirable feature--instead, it's a necessity to protect essential personal and business data from hackers and eavesdroppers. In this handy reference, Praphul Chandra gives you the conceptual and practical tools every RF, wireless, and network engineer needs for high-security wireless applications. Book Review From EDN Magazine: http://www.edn.com/article